Plotagon Training for English Teachers during the Covid-19 Pandemic (LingPoet: Journal of Linguistics and Literary Research, 2024)
A great majority of English teachers agree that it is crucial for them use to use digital technology to help students improve their foreign language skills. Many studies, however, show that the number of teachers who use technology in their teaching and learning practices is still limited. The lecturing method, discussion method, and follow-up study method were used to undertake the training activities. This study presents an overview of the training participants' reactions to the use of Plotagon in English learning, as well as the extent to which the participants understand how to create English dialogues using Plotagon. The use of online training turned out to have a significant impact on the characteristics of participants who interacted during the training. This technical skill weakness, however, could be compensated for by responding quickly when asked by the material provider via video conference. They believed that online tools should only be used as a supplement to the training process. Despite this, the majority of participants agreed that Plotagon was very useful for improving the quality of English learning, so the participants were enthusiastic about participating in the training even with all these obstacles. Keywords: Community service; digital technology; English teaching; online; Plotagon